Making Sense of Arab Labor Markets: The Enduring Legacy of Dualism - Ragui Assaad (Institute for the Study of Labor (IZA), 2013)
It is well-established that Arab labor markets share certain common characteristics, including an oversized public sector, high unemployment for educated youth, weak private sector dependent on government welfare for their survival, rapid growth in educational attainment, but much of it focused on the pursuit of formal credentials rather than productive skills, and low and stagnant female labor force participation rates. I argue in this paper that all of these features can be explained by the deep and persistent dualism that characterizes Arab labor markets as a result of the use of labor markets by Arab regimes as tool of political appeasement in the context of the authoritarian bargain social contract that they have struck with their citizens in the post-independence period. Even as fiscal crises have long destabilized these arrangements in most non-oil Arab countries, culminating in the dramatic political upheavals of the Arab spring revolutions, the enduring legacy of dualism will continue to strongly shape the production and deployment of human capital in Arab economies for some time. This will undoubtedly pose serious challenges to any efforts to transform these economies into dynamic, rapidly growing and more equitable globally competitive economies.
Keywords: I25; J21; J24; J31; J45; O53; P52; 330; labor market dualism; Arab Spring; unemployment; education; authoritarian bargain